2021
DOI: 10.1002/dac.5037
|View full text |Cite
|
Sign up to set email alerts
|

A wide circularly polarized dual‐band isosceles trapezoidal monopole antenna with modified ground plane

Abstract: Summary In this paper, a simple wideband circularly polarized monopole antenna for different wireless and satellite communication applications is proposed. The top plate of the antenna is composed of an isosceles trapezoidal patch with an inverted L‐shaped strip connected along with this. The bottom side (ground plane) has been modified by embedding two right‐angle triangular stubs for enhancing the impedance and CP performances. The proposed antenna is designed and fabricated on commercially available FR4 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In references, 14–17 coplanar strip, simple strip, slot and half cutting CP antenna techniques, and inverted L‐ shaped PS with microstrip line had been developed for CP radiation. Semicircular patch antenna, 18 metal ridge septum with rectangle and triangle cascade, 19 trapezoidal monopole antenna, 20 two parasitic strips loaded CP antenna, 21 coplanar waveguide feeded T ‐shaped monopole antenna with inverted L ‐shaped grounded stub, 22 modified rectangular monopole, asymmetric ground plane, L ‐shaped strip with CPW feed, 23 and a DRA for circular polarization 24 were implemented for broadband, dual‐band, and dual‐sense applications. From the above literature survey, it is observed that the ARBW is improved with large antenna size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In references, 14–17 coplanar strip, simple strip, slot and half cutting CP antenna techniques, and inverted L‐ shaped PS with microstrip line had been developed for CP radiation. Semicircular patch antenna, 18 metal ridge septum with rectangle and triangle cascade, 19 trapezoidal monopole antenna, 20 two parasitic strips loaded CP antenna, 21 coplanar waveguide feeded T ‐shaped monopole antenna with inverted L ‐shaped grounded stub, 22 modified rectangular monopole, asymmetric ground plane, L ‐shaped strip with CPW feed, 23 and a DRA for circular polarization 24 were implemented for broadband, dual‐band, and dual‐sense applications. From the above literature survey, it is observed that the ARBW is improved with large antenna size.…”
Section: Introductionmentioning
confidence: 99%
“…rectangle and triangle cascade, 19 trapezoidal monopole antenna, 20 two parasitic strips loaded CP antenna, 21 coplanar waveguide feeded T-shaped monopole antenna with inverted L-shaped grounded stub, 22 modified rectangular monopole, asymmetric ground plane, L-shaped strip with CPW feed, 23 and a DRA for circular polarization 24 were implemented for broadband, dual-band, and dual-sense applications. From the above literature survey, it is observed that the ARBW is improved with large antenna size.…”
mentioning
confidence: 99%
“…This paper presents the design of a multiband coplanar waveguide antenna using a graphene film over a glass substrate. The proposed antenna presents omnidirectional radiation and operates in two bands, first in the 2.45 GHz ISM band and the second band covering the frequency range from 4 to 6 GHz to generate the multiband behavior; the antenna is formed by two resonator patches, as reported in [ 33 , 34 , 35 , 36 ]. The antenna is fully characterized by the reflection coefficient and the radiation patterns’ measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The circularly polarized antenna is not sensitive to the polarization of electromagnetic waves, can receive electromagnetic waves in any form of polarization, and also can avoid polarization loss caused by polarization mismatch. [4][5][6] The methods to achieve circular polarization include the single-feed method, 7,8 multi-feed method, [9][10][11] and the use of polarization converters. 12,13 The polarized reconfigurable antennas [14][15][16] can be converted between circular polarization and linear polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of electromagnetic signals in space is becoming increasingly complex, and more and more interference factors have put forward a major challenge to the stability of wireless communication systems. The circularly polarized antenna is not sensitive to the polarization of electromagnetic waves, can receive electromagnetic waves in any form of polarization, and also can avoid polarization loss caused by polarization mismatch 4–6 . The methods to achieve circular polarization include the single‐feed method, 7,8 multi‐feed method, 9–11 and the use of polarization converters 12,13 .…”
Section: Introductionmentioning
confidence: 99%